2012
DOI: 10.5897/ajbm11.2467
|View full text |Cite
|
Sign up to set email alerts
|

Micro business enterprise of Bumiputera Malays, Malaysia

Abstract: This research focuses on micro-enterprise of Malaysian Malays that are involved in very small-scaled business activities. Among them include food stall and burger stall operators, night market hawkers, grocery store operators as well as construction and small service activities works. The study seeks to explore why some micro-entrepreneurs still lag in entrepreneurship and what needs to be rectified. This quantitative study is conducted on 173 Malay micro-enterprise owners (MEOs) and 58 Malay failed micro-ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Entrepreneur training generally defined as an education in the enterprise has a more profound impact than education. Lack of technical know-how often acts as a barrier in the technological development of small and medium enterprises (SME) (Jamak et al, 2012). According to Panda (2008), strong technical competencies provide a base for decision making related to raw material selection, selection of suitable technology and also entrepreneurship development (Baum et al, 2001).…”
Section: Entrepreneurial Development Trainingmentioning
confidence: 99%
“…Entrepreneur training generally defined as an education in the enterprise has a more profound impact than education. Lack of technical know-how often acts as a barrier in the technological development of small and medium enterprises (SME) (Jamak et al, 2012). According to Panda (2008), strong technical competencies provide a base for decision making related to raw material selection, selection of suitable technology and also entrepreneurship development (Baum et al, 2001).…”
Section: Entrepreneurial Development Trainingmentioning
confidence: 99%
“…Further, in lifting the Malays out of poverty (and increasing their economic status), the Malaysian Government encourages business participation and provides business-related assistance and incentives to entrepreneurial Malays (Abdul Jamak et al, 2012;Wan Husin, 2013). As a result of these affirmative actions, several Malay products and services have succeeded in entering the market with a certain degree of success.…”
Section: Introductionmentioning
confidence: 99%
“…To attain business growth, the most noteworthy issue of concern is the psychological factors of MEs. Some previous studies found that personal characteristics have a relationship with the business growth of MEs (Jamak et al 2012). Despite the importance of personal characteristics and its effects on the business growth of MEs, the focus of most past studies in Malaysia was mostly limited to the adoption of Information, Communication and Technology (ICT), financial assistance, and technical efficiency in SMEs (Nawai, Shariff 2011;Radam et al 2008).…”
Section: Introductionmentioning
confidence: 99%